Reflections on "Internet+" Innovation and Entrepreneurship Talent Training - Zhao, Zengjun (Journal of Education and Educational Technologies, 2023)
In the context of "Internet plus", information technology is the key technology to lead social development and progress. It is essentially changing the way of production and lifestyle of society. All walks of life are constantly adjusting their development models to adapt to the Internet era and achieve their own rapid development. Therefore, education should follow the trend and provide more practical talents for the society through education. Combining the current needs of social development and the requirements of the "Internet plus" era for talents, the article has carried out in-depth thinking on the training of "Internet plus" entrepreneurial and innovative talents and explored effective training strategies.